A comprehensive investigation of plowing and grain-workpiece micro interactions on 3D ground surface topography. (August 2018) - Zhou, Weihua; Tang, Jinyuan; Chen, Haifeng; Zhu, Caichao; Shao, Wen
Highlights: A new model for predicting the grinding surface morphology based on the measured surface of the grinding wheel is established, which takes the plowing effect into consideration. A new method of calculating the instantaneous undeformed chip thickness is established. The ground workpiece surface morphology is predicted accurately by comparing with experimental result. The different influence of surface morphology caused by cutting trajectory and plowing effect is studied. Abstract: The accumulation of plowing effect in the grinding process which is ignored in previous researches has an essential influence on the surface topography of the workpiece. In this study, a new grinding surface topography modeling method considering the plowing effect is proposed. The modeling method of the grinding wheel based on the replicated method is given to obtain the real and accurate wheel surface topography. According to the cutting path of abrasive particles extracted from the wheel topography, the instantaneous undeformed chip thickness is calculated to determine the contact stages of rubbing, plowing and cutting. The influence of material accumulation caused by the plowing effect on the microstructure is discussed, and the mechanism of complex changes in the surface topography resulting from the interference between the grains is analyzed to generate the grinding surface topography. Based on the proposed model, the effects of plowing effect and grain-workpiece micro interactions on 3D ground surface topography have been studied. And topography parameters ( Sa, Sp, Sv, Sku ) are utilized to evaluate the difference between the simulated result and experimental result. It has been found that the experimental result is in good agreement with the surface topography model and plowing effect could not be ignored. The modeling method of grinding surface topography considering the influence of the plowing stacking effect in this study may serve as a novel and more practical way to predict the grinding surface topography. Graphical abstract: Image, graphical abstract